Aliran Kalam Murji’ah - Abdillah, Rifqy (Maliki Interdisciplinary Journal, 2024)
The Islamic faction known as the Murji’ah is seen as impartial and offers optimism to individuals who commit grave sins. Murji’ah represents a theological current within Islam that extends hope to those who have committed major transgressions. The genesis of this faction stemmed initially from political tensions but also intersected with theological dilemmas. Etymologically, Murji’ah derives from "Al-irja’", signifying "end", or possibly from "Irja" meaning "suspension". In this context, Murji’ah denotes a faction that contends a person’s faith remains intact despite their commission of major sins. This article employs literary research methodologies, utilizing sources such as literature, periodicals, books, and online publications to delve into Murji’ah’s ideologies. Nonetheless, Murji’ah’s doctrines are deemed erroneous and inconsistent with the teachings of the Quran and Sunnah throughout history to the present day. For those espousing deviant perspectives, Murji’ah ideology might serve as a means to circumvent adherence to Sharia laws.